Time-varying fiscal policy in the U.S. - Pereira, Manuel Coutinho (2022)
To investigate time heterogeneity in the e¤ects of fiscal policy in theU.S., we use a non-recursive, Blanchard and Perotti-like structural VAR with time-varying parameters, estimated through Bayesian simulation over the 1965:2-2009:2 period. Our evidence suggests that fiscal policy has lost some capacity to stimulate output but that this trend is more pronounced for taxes net of transfers than for government expenditure, whose e¤ectiveness declines only slightly. Fiscal multipliers keep conventional signs throughout. An investigation of changes in fiscal policy conduct indicates an increase in the countercyclical activism of net taxes over time, which appears to have reached a maximum during the 2008-09 recession.